2018
DOI: 10.3899/jrheum.170994
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Utility of the 6-minute Walk Test in Systemic Sclerosis

Abstract: We show strong reproducibility for the 6MWD and confirm the 6MWT utility to assess the overall prognosis of patients with SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Still, this study was small ( N = 25), and it was only possible to obtain reliable measurements using the earlobe probe in a minority of patients ( n = 7). In our study, the post-exercise Borg dyspnoea score and the 6MWD were similar at both visits which is in line with other studies that also found good reproducibility of the 6MWD in patients with SSc [ 7 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Still, this study was small ( N = 25), and it was only possible to obtain reliable measurements using the earlobe probe in a minority of patients ( n = 7). In our study, the post-exercise Borg dyspnoea score and the 6MWD were similar at both visits which is in line with other studies that also found good reproducibility of the 6MWD in patients with SSc [ 7 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Total distance walked (6-min walking distance, 6MWD) was recorded. The predicted six-minute walk distance (6MWD) for women was calculated based on the following formulas (2.11 × height) − (2.29 × weight) − (5.78 × age) + 667 m. The 6MWD was considered abnormal if it was <80% of the normal range predicted by Enright’s equation [ 49 ]. We considered a distance walked of at least 350 m as the inclusion criterion [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we did not observe a significant correlation between the 6MWD and mRSS. In contrast, the study by Pugnet et al (39) showed that the mRSS is an independently associated factor with a lower 6MWD. Since the sample evaluated by Pugnet et al (39) had a worse mRSS, skin damage might have negatively impacted movement limitations during the 6MWT.…”
Section: Discussionmentioning
confidence: 78%